Potential of Elateriospermum tapos blume extract as conjugation inhibitor for preventing dissemination of tetracycyline resistance gene transfer - Mohd Ghazali, Nur Ainaa Nabihah (2021)
Dissemination of antibiotic resistance has caused major threat to human health especially in causing hospital-acquired infections. Horizontal gene transfer, mainly conjugation is the responsible transfer mechanism of antibiotic resistance genes among antibiotic resistant bacteria. The search for specific compounds or molecules that are able to inhibit conjugation is therefore significant for preventing antibiotic resistance gene transfer. Unsaturated fatty acids specifically oleic, linoleic and alpha-linolenic acids are known as conjugation inhibitors due to their conjugation inhibition ability, although most of the previous studies used synthetic unsaturated fatty acids. In this study, Elateriospermum tapos seed oil (ETSO) with high unsaturated fatty acids composition was obtained using Soxhlet extraction method and used to determine its potential in preventing conjugal transfer of tetracycline resistantgene (tetM). Antimicrobial susceptibility testing was carried out to determine resistance profiles of bacterial strains prior to conjugation assay. Filter mating experiment between Lactococcus garvieae KHS-97051, Enterococcus faecalis JH2-2, Clostridium difficile ribotype 014 and Enterococcus faecalis ATCC 51299 were conducted to determine suitable donor and recipient cells for conjugation inhibition study. Successful transfer of tet(M) gene in transconjugants was confirmed by colony re-streaking, Gram-staining and polymerase chain reaction (PCR). E. faecalis JH2-2 transconjugants conferring tet(M) resistance were produced from mating between L. garvieae KHS-97051 donor and E. faecalis JH2- 2 recipient. Transfer frequency decreased from (6.11 ± 1.80) x 10-6 to (5.99 ± 3.44) x 10-10 transconjugant per donor and (5.85 ± 1.58) x 10-8 to (5.89 ± 2.31) x 10-10 transconjugant per recipient after exposed to ETSO. Transconjugant colonies following ETSO exposure was reduced from 163 to 9 colonies with 94.48% of conjugation inhibition. Although, no transconjugant was observed from two conjugation sets of C. difficile donor and E. faecalis JH2-2 and E. faecalis ATCC 51299 recipients proven that mating is a donor-recipient specific event. Scanning (SEM) and transmission electron microscopy (TEM) were used to identify the effects of ETSO exposure towards donor and recipient cells during conjugation. The average size of pili produced from control and ETSO exposed mating cells were 0.213 ± 0.029 and 0.093 ± 0.042 μm, respectively hence demonstrated that there is significant difference between the two groups. Aside from conjugative pili, there was no appearance of short, numerous attachment pili known as fimbriae on the cell surface of both cells. However, less cell-to-cell contact and pili formations were captured in the exposed donor and recipient cells. Smooth continuous cell wall and membrane of non-exposed recipient cell was observed but the cell thickness increased in the exposed recipient cell. There was no difference in cell diameter before and after ETSO exposure. No damaging effects were observed towards the exposed cells. The COIN potential of ETSO highlighted in this study will extend the current knowledge on the antimicrobial resistance in bacteria and enable the future development of a promising alternative bottom-up strategy to control the emergence and spread of antimicrobial-resistant bacteria.